MENAKAR BAHASA DALAM SASTRA: PERBINCANGAN SEPUTAR TATA BAHASA DAN SASTRA - Jejen Jaelani (Jurnal Sosioteknologi, 2011)
Grammar plays an important role as a foundation for writing activities. However, many people who feel reluctant when hearing the phrase "grammar". This can be understood as a grammar lesson at our school is monotonous and uncreative. Language learning is not placed within the framework of creativity. It also happens in the practice of literary writing. Many people who feel no need to learn grammar. In fact, the act of writing is an activity to create literary language and imagination. Grammar has a significant role in the writing of literature. Key words: grammar, literature, creativity, imagination